Prevalence and Factors Affecting Lower Back Pain Among Nurses in Rehabilitation Hospital Cheras, Malaysia - Mazni, Nur Izzati Mohd; Bekti, Yoyok; Ab Latif, Rusnani (Health Dynamics, 2025)
Background: Nurses are a high-risk profession group that experiences lower back pain (LBP). Nurses who suffer from LBP may have difficulty standing up from a sitting position and lifting patients. One of the reasons that cause a high number of cases of lower back pain among nurses is the constant handling of patients manually, such as moving or transferring patients using the nurses’ body strength. This study was conducted to determine the number of nurses who have lower back pain in Cheras Rehabilitation Hospital as well as the factors contributing to their LBP. Methods: A quantitative, cross-sectional, and, survey-based design was used as the research methodology to conduct this study. A total of 211 nurses in Cheras Rehabilitation Hospital were selected for this study. Results: The outcome indicated that the frequency of LBP occurrences is indeed higher among nurses, with 60.7% reporting LBP due to their job involving prolonged patients lifting. The problem of LBP developed among them after they began working as nurses, and most of them did not seek treatment to cure their LBP. Among the factors that contribute to the problem of LBP are lifting patients frequently, standing for long periods, the type of discipline work in, and working hours per week. Conclusions: Addressing these issues through ergonomic interventions, safe patient handling practices, and policies to reduce prolonged standing and excessive work hours is crucial for improving nurses' occupational health and well-being.